Effect of medical and nursing teaching program on awareness and adherence among elderly patients with chronic heart failure in Assiut, Egypt - Soheir M Kasem Ahmed; Nermeen Mahmoud Abd El-Aziz (SpringerOpen, 2017)
Introduction Heart failure (HF) among geriatric population is an eminent problem, and patient awareness of the disease and subsequent adherence to the treatment may decrease the burden of this serious problem. Objective The purpose of the study is to evaluate the effectiveness of medical as well as nursing teaching program on awareness and adherence among elderly patients with chronic HF. Patients and methods The study was carried out in the Internal Medicine Department of Assiut University Hospital. Total coverage sample of elderly patients included 100 patients from both sexes, and their age ranged from 60 to 75 year. The study was carried out in the Internal Medicine Department of Assiut University Hospital. Overall, three tools were used in this study: (a) patient interviewing sheet (pretest and post-test) tool consisting of two parts regarding demographic characteristic and medical data, (b) Atlanta HF knowledge test, and (c) adherence questionnaire. Results The main results yielded by the study proved a highly statistically significant difference between pretest and post-test regarding awareness and adherence for patients. Conclusion and recommendations This study concluded that the medical and nursing teaching program was effective for awareness and adherence of the patients. More follow-up studies are needed to improve awareness and adherence for older adult patients with chronic HF to prevent complications.